Variation in anisotropic shrinkage of plantation-grown Pinus radiata wood - Wang, Eric; Chen, Taian; Pang, Shusheng; Karalus, Andrew (Maderas. Ciencia y Tecnología, 2025)
Anisotropic shrinkage of 27-year old Pinus radiata wood was measured from green to oven-dry condition. The samples were prepared from 21 discs cut from seven trees at different stem heights of 0.1m, 5.2m and 10.3m above ground, respectively. Longitudinal shrinkage was found to vary from 0.02% to 2.34%, with peak values near the pith decreasing towards the bark. The variation was more pronounced at the 0.1m height. The longitudinal shrinkage also showed a trend of decrease with the stem height above the ground. Tangential and radial shrinkage was found to increase with growth ring number from the pith, but the variation along the stem height did not show a clear trend. The results confirmed that the pith-to-bark variation and vertical variation of the anisotropic shrinkage were significant for radiata pine. Large differences were also observed among corewood, transition wood and outerwood. Microfibril angle (MFA) was believed to the main reason for these variations.